Effect of time of sample collection after onset of diarrhea on fecal microbiota composition of calves - Lynna Li; David L. Renaud; Hanne M. Goetz; Emma Jessop; Marcio C. Costa; Lisa Gamsjäger; Diego E. Gomez (Journal of Veterinary Internal Medicine, 2023)
Abstract Background The effect of time of sample collection after onset of diarrhea on the fecal microbiota composition of calves is unknown. Objective Compare the fecal microbiota of calves with diarrhea onset on the day of sampling (D <24h), and calves having had diarrhea for >24 to 48 hours (D 24‐48h). Animals Thirty‐one diarrheic calves (20 D <24h and 11 D 24‐48h), 3 to 7 days of age. Methods Cross‐sectional study. Diarrhea was defined as a calf with loose feces or watery feces. Assessment of the fecal microbiota was performed by sequencing of 16S ribosomal RNA gene amplicons. Results Richness and diversity were not statistically different between D <24h and D 24‐48h (P > .05), but bacterial membership and structure differed significantly (AMOVA, P < .001 for both comparisons). Linear discriminant analysis effect size (LefSe) showed an enrichment of Faecalibacterium, Phocaeicola, Lachnospiracea, and Lactobacillus in the feces of D <24h calves, whereas Escherichia/Shigella, Ligilactobacillus, Clostridium_Sensu_Stricto, Clostridium_Incerta_Sedis, and Enterococcus were enriched in the D 24‐48h calves. Conclusion and Clinical Importance Rapid changes in fecal microbiota occur during the first 48 hours of diarrhea with an enrichment of lactic acid‐producing bacteria in D <24h followed by an enrichment in Escherichia/Shigella and Clostridium spp. in D 24‐48h. The time from diarrhea onset to sampling appears to affect the bacterial composition. Researchers should standardize times for fecal collection based on the time of diarrhea.